Financial Strength and Product Market Competition: Evidence from Asbestos Litigation - Hadlock, Charles J.; Sonti, Ramana (Journal of Financial and Quantitative Analysis, 2012)
Abstract We study the role of financial strength on product market competition by examining exogenous shocks to a firm’s liability structure arising from asbestos litigation. We find that exogenous increases (decreases) in asbestos liabilities are interpreted by the market as negative (positive) news for a firm’s close competitors. These reactions are magnified in events in which one asbestos-tainted firm goes bankrupt and other asbestos-tainted stocks fall on the news of the bankruptcy. For smaller competitors, market reactions are more pronounced in more concentrated industries. Our findings support the general hypothesis that increases in fixed liabilities lead to more aggressive product market interactions.